2014
DOI: 10.1111/trf.12973
|View full text |Cite
|
Sign up to set email alerts
|

SARA: a “new” low‐frequencyMNSantigen (MNS47) provides further evidence of the extreme diversity of theMNSblood group system

Abstract: We provide evidence that the SARA antigen is encoded by a SNV on GYPA and SARA has been reassigned to the MNS blood group system, now MNS47. This discovery provides a basis for application of genetic approaches in SARA typing when clinically indicated, for example, in HDFN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…Molecular‐based methods, that is, DNA genotyping on SNP microarray, whole‐exome sequencing, and genome‐wide association study using DNA databases, have been developed recently and have revealed the causal genes of the blood group antigens such as ABCG2 (Jr a ), SMIM1 (Vel), GYPA (SARA, MNS47), and PRNP (KANNO) . Before adoption of these methods to identify the causal gene of the SUMI antigen, we successfully identified the carrier molecule of the SUMI antigen as GPA by conventional ICFA using HIRO‐305.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular‐based methods, that is, DNA genotyping on SNP microarray, whole‐exome sequencing, and genome‐wide association study using DNA databases, have been developed recently and have revealed the causal genes of the blood group antigens such as ABCG2 (Jr a ), SMIM1 (Vel), GYPA (SARA, MNS47), and PRNP (KANNO) . Before adoption of these methods to identify the causal gene of the SUMI antigen, we successfully identified the carrier molecule of the SUMI antigen as GPA by conventional ICFA using HIRO‐305.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been shown that MPS can be applied for accurate blood group genotyping and RBC antigen prediction . Whole exome sequencing has proven to be an efficient way to define the genetic basis for “orphan” antigens and to provide a precise RH genotype in patients with sickle cell anemia . Whole genome sequencing has been proposed as an alternative to targeted sequencing to provide a full blood group genotype profile but this approach generates an enormous amount of data, much of which is inconsequential to blood group genotyping .…”
Section: Discussionmentioning
confidence: 99%
“…6,8 Whole exome sequencing has proven to be an efficient way to define the genetic basis for "orphan" antigens and to provide a precise RH genotype in patients with sickle cell anemia. [35][36][37] Whole genome sequencing has been proposed as an alternative to targeted sequencing to provide a full blood group genotype profile but this approach generates an enormous amount of data, much of which is inconsequential to blood group genotyping. 6 Fichou and colleagues 7 demonstrated that targeted MPS could be applied for routine blood group genotyping in specific populations such as sickle cell disease patients.…”
Section: Discussionmentioning
confidence: 99%
“…An elegant example, modelled on approaches used in discovering mutations for rare diseases, employed a WES strategy on family members of a donor carrying the then “orphan antigen”, designated the SARA antigen. The SARA antigen was first described in 1990 in an Australian blood donor and in 2011 it was described in a Canadian maternity case where a maternal antibody was implicated in a case of severe haemolytic disease of the fetus and newborn (HDFN) (McBean et al , ).…”
Section: Resolving Orphan Antigens By Wes: a Rare Disease Approachmentioning
confidence: 99%
“…This leads to a p.Arg80Ser amino acid change on GYPA, the glycoprotein carrying the M and N antigens of the MNS blood group system. The SARA antigen is now registered as MNS antigen number 047 by the ISBT (McBean et al , ). Interestingly serology reagents were unable to implicate the MNS system because the amino acid change alters the ‘enzymatic reactivity’ pattern during routine serology investigations.…”
Section: Resolving Orphan Antigens By Wes: a Rare Disease Approachmentioning
confidence: 99%